Integrating Supply and Demand - Tate, Wendy; Mollenkopf, Diane; Stank, Theodore; Da Silva, Andrea; Davis, Edward; Christopher, Martin; Fisher, Marshall; Jonsson, Patrik; Mersereau, Adam; Raman, Ananth (MIT Sloan Management Review, 2015)
If an organization only makes incremental improvements, it should expect only incremental increases to its profits. More dramatic gains in profitability require a radical overhaul to high-level organizational thinking. Our research suggests that demand and supply integration offers one such pathway to creating a culture that recognizes that an organization cannot simultaneously be all things to all customers. Instead, demand and supply integration helps companies get ahead by enabling organizations to make tough decisions about how to allocate scarce resources to optimize creation of value - and for which customers.